2017
DOI: 10.1111/wej.12324
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on two integrated membrane systems for the reuse of electroplating wastewater

Abstract: A pilot study was done on a nanofiltration (NF)‐reverse osmosis (RO) and RO‐NF integrated membrane system about the feasibility of membrane for electroplating rinse wastewater treatment in concentrate stage configuration. Nickel sulphate solution was used as a synthetic wastewater. Water recovery, metal rejection and specific entropy production (SEP) were investigated under different operation pressure, feed temperature and feed concentration. The results showed water recovery of RO‐NF system was more than 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The separation efficiency of the RO–NF system has been proved to be higher than that of the NF–RO system. 171…”
Section: Resource Utilization Technology Of Electroplating Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…The separation efficiency of the RO–NF system has been proved to be higher than that of the NF–RO system. 171…”
Section: Resource Utilization Technology Of Electroplating Wastewatermentioning
confidence: 99%
“…Membrane fouling is an unavoidable problem with the current integrated membrane technology and is one of the main costs associated with the use of membrane technology in plants, the mechanisms of which are: (1) formation of the filter cake layer; (2) blockage of the membrane pores; (3) adsorption within the membrane pores. 171 The use of integrated membrane technology requires close attention to three aspects: the physical and chemical properties of the membrane itself, the water quality conditions and the operating parameters. Researches have shown that high organic content in water bodies can significantly increase the degree of membrane contamination.…”
Section: Resource Utilization Technology Of Electroplating Wastewatermentioning
confidence: 99%